Biaxial strain tuned thermoelectric properties in monolayer PtSe2 - Guo, San-Dong (Journal of materials chemistry. C, Materials for optical and electronic devices, 2016)
Strain engineering is a very effective method to tune the electronic, optical, topological and thermoelectric properties of materials. In this work, we systematically study the biaxial strain dependence of electronic structures and thermoelectric properties (both electron and phonon parts) of monolayer PtSe2 with generalized gradient approximation (GGA) plus spin-orbit coupling (SOC) for the electron part and GGA for the phonon part. The calculated results show that compressive or tensile strain can induce a change in the position of the conduction band minimum (CBM) or valence band maximum (VBM), which produces important effects on the Seebeck coefficient. It is found that compressive or tensile strain can induce significantly enhanced n- or p-type Seebeck coefficients at the critical strain of change for the position of the CBM or VBM, which can be explained by strain-induced band convergence. Based on GGA+U+SOC, the electron correlation effects on the electron transport coefficients are also considered, the corresponding results agree well with those using GGA+SOC. Another essential strain effect is that tensile strain can produce significantly reduced lattice thermal conductivity, and the room temperature lattice thermal conductivity at the strain of -4.02% can decrease by about 60% compared to the unstrained one, which is very favorable for high ZT. To estimate the efficiency of thermoelectric conversion, the figure of merit ZT can be obtained by the empirical scattering time tau . The calculated ZT values show that strain is indeed a very effective strategy to achieve enhanced thermoelectric properties, especially for p-type doping. Tuning thermoelectric properties with strain can also be applied to other semiconducting transition-metal dichalcogenide monolayers MX2 (M = Zr, Hf, Mo, W and Pt; X = S, Se and Te).